2022
DOI: 10.3389/fphar.2022.1039416
|View full text |Cite
|
Sign up to set email alerts
|

Phase I pharmacokinetic study of an oral, small-molecule MEK inhibitor tunlametinib in patients with advanced NRAS mutant melanoma

Abstract: Background: Malignant melanoma is an aggressive disease. Tunlametinib (HL-085) is a potent, selective, and orally bioavailable MEK1/2 inhibitor. The objective of this study was to determine the pharmacokinetics (PK) of tunlametinib and its main metabolite M8 in patients with NRAS-mutant melanoma following a single dose and multiple doses in a phase I safety and PK study.Methods: A multiple-center phase I study was performed in patients with melanoma including dose-escalation phase and dose-expansion phase. PK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Overall, our findings constitute a preclinical data of tunlametinib and offer a precision medicine option available that could be tailored to individual mutations and cancers. These data supported the progression of tunlametinib into a first-in-human clinical study ( Zhao et al, 2022 ; Wang et al, 2023 ). Currently, the first-in-human phase 1 ( ClinicalTrials.gov number, NCT03973151, NCT04683354) and pivotal clinical study of tunlametinib (NCT05217303) as monotherapy, and the phase 1 study as combination therapy (NCT05263453) have been completed.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Overall, our findings constitute a preclinical data of tunlametinib and offer a precision medicine option available that could be tailored to individual mutations and cancers. These data supported the progression of tunlametinib into a first-in-human clinical study ( Zhao et al, 2022 ; Wang et al, 2023 ). Currently, the first-in-human phase 1 ( ClinicalTrials.gov number, NCT03973151, NCT04683354) and pivotal clinical study of tunlametinib (NCT05217303) as monotherapy, and the phase 1 study as combination therapy (NCT05263453) have been completed.…”
Section: Discussionsupporting
confidence: 76%
“…Tunlametinib emerged as the top candidate from an optimization of molecular structure, as this compound incorporated both improved potency and favorable PK properties. Trametinib, as the first approved MEK inhibitor, has blood drug accumulation with the mean accumulation ratio (day15/day1) with repeat dose of 2 mg approximate 6.0 ( Food and Drug Administration, 2013 ), whereas tunlametinib showed minimal drug accumulation in preclinical and clinical studies ( Zhao et al, 2022 ). Compared with other three FDA-approved MEK inhibitors, tunlametinib showed much more potent both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HL-085 exposure (area under the curve and maximum plasma concentration) is close to dose proportional over the dose range of 0.5-15 mg twice daily with minimal accumulation. The mean plasma terminal half-life is 21.84 h-34.41 h. More detailed results of the pharmacokinetic analysis of the parent study are described in another article which was recently published by Qian Zhao et al [23].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Tunlametinib (HL-085) is a novel, selective inhibitor of MEK that exhibits high inhibitory activity against MEK1 and moderate activity against MEK2, developed by Shanghai Kechow Pharma, Inc., Shanghai, the People’s Republic of China [ 15 ]. In preclinical studies, tunlametinib showed antitumor activity in a variety of tumor cell lines and tumor xenograft models.…”
Section: Introductionmentioning
confidence: 99%